ANALYSIS OF ROE AND BOPO OF INDONESIA SHARIA BANK COMPANY ON FINANCIAL PERFORMANCE: USING EVIEWS 9 - Rohana Faridah; Lisda Aisyah (IAIN Surakarta, 2023)
This research is motivated by the merger between Bank Rakyat Indonesia Sharia (BRIS) company which change into Indonesia Sharia Bank (BSI) company. Several factors influence it, one of which is the stock price. This share price is also influenced by financial ratios including ROE and BOPO. ROE and BOPO have reports that are very influential on BSI's share price because in sharia banking reports the second value has a significant value in the financial statements in the quarter when BRIS merged into BSI. This type of research was a quantitative descriptive research. The company was Indonesia Syaria Bank company. The data used in this research was secondary data in the form of time series data obtained from the financial reports of Indonesia Syaria Bank company. The analysis technique used multiple linear regression analysis with the help of the Eviews 9 program. The results show that simultaneously the ROE and BOPO financial ratios have a significant effect on stock prices. Partially, the financial ratio variable ROE has an effect but not significantly on stock prices. Meanwhile, the financial ratio variable BOPO partially has a negative and significant effect on stock prices.